Penerapan Model Pembelajaran Kuantum Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas II SD Negeri 4 Pertima - Ni Gusti Made Sutari (Jayapangus Press, 2019)
This Classroom Action Research aims to describe the process of using quantum learning that can improve student learning outcomes and to analyze improvement in student learning outcomes after the use of concrete teaching aids. Classroom Action Research Procedures are carried out through a grooved process consisting of 4 stages, namely: 1) planning, 2) implementation, 3) Observation, and 4) reflection. From the data analysis it is known that in each cycle there is an increase in completeness of student learning outcomes. In the initial study, students who achieved completeness were only 45%. In the first cycle the number of students who achieved completeness increased by 14% from the initial study to 59% and in the second cycle it increased to 100%. The same thing also happened to the sincerity of student learning. Based on the results of this research data analysis it can be concluded that the use of concrete teaching aids can improve the learning outcomes of Class II SD students in science learning the concept of the main parts of animals and plants.